(untitled) (Revista de Estudios Europeos, 2026)
This article aims to question the legal viability of two concepts, administrative silence and administrative inactivity, created in a very different legal, technological and social context than the current 21st century. The objective is to recall their initial motivation and reflect on whether their use by the Administration is justified o represents a manifestation of mismanagement. The UE has not a specific regulation of the deadline to answer the citizens’ claims. It is examined the possible abuse of applying then in a European and national level, and questioning why they have become standard responses in general, to address citizens’ requests. Finally, the article analyzes, if this fits into the principle of good administration set for the Chapter of Fundamental Rights of the European Union and the Agenda 2030 (SDG, 16).